Heating up to keep cool: benefits and persistence of a practical heat acclimation protocol in elite female olympic team-sport athletes - Fenemor, S. P.; Gill, N. D.; Anderson, B.; Casadio, J. R.; Sims, S. T.; Beaven, C. M. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Although recommendations for effective heat acclimation (HA) strategies for many circumstances exist, best-practice HA protocols specific to elite female team-sport athletes are yet to be established. Therefore, the authors aimed to investigate the effectiveness and retention of a passive HA protocol integrated in a female Olympic rugby sevens team training program.